Women's Rights Under International, American, Islamic, and Egyptian Law: An Irresolvable Conflict : A Cross-cultural Examination of Gender Equality - Ibrahim, Mohammad, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
This book presents a comprehensive analysis of women's rights pertaining to abortion, employment equality, and the choice to wear a hijab under international, American, Islamic, and Egyptian law. It challenges the notion that Islamic Shari'a inherently discriminates against women and attributes these perceptions to cultural stereotypes and social norms. It highlights the discrimination Muslim women encounter in Western countries and advocates for the protection and promotion of their rights to foster equality, fairness, diversity, and social cohesion. Essential reading for anyone interested in gender equality, it offers a fresh perspective on the intersections between law, culture, and women's rights.